Regulation and control method of single-stage microporous metal oil-water separation membrane with high permeability and high selectivity

By optimizing the pore size and pore wall thickness of the single-stage microporous structure in the porous metal separation membrane, combining gradient experiments and philosophical formulas, the problem of taking into account high permeability and high selectivity is solved, and the efficient oil-water separation effect is achieved.

CN119528266AActive Publication Date: 2025-02-28NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
CN202411700191.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing porous metal separation membranes are difficult to balance between achieving high permeability and high selectivity, resulting in limited permeability and separation efficiency.

Method used

Using a structural-functional integrated design scheme, the pore size and pore wall thickness (R/D value) of a single-stage micropore structure are optimized to achieve high selectivity and high permeability through the combination of gradient experiments and philosophical formulas.

Benefits of technology

The high permeability and selectivity of a single-stage microporous metal oil-water separation membrane is achieved, breaking through the flux bottleneck of the traditional layered structure, and improving the mechanical durability and application breadth of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528266A_ABST
    Figure CN119528266A_ABST
Patent Text Reader

Abstract

The invention discloses a regulation and control method of a single-stage microporous metal oil-water separation membrane with high permeability and high selectivity, which comprises the following steps of: 1, obtaining a aesthetic formula and empirical parameters a, b and c through a gradient experiment; 2, deducing a minimum value of f according to empirical parameters a, b and c to obtain a corresponding R / D; and 3, obtaining the single-stage microporous metal oil-water separation membrane with high permeability and high selectivity by adopting the obtained R / D. According to the single-stage microporous metal oil-water separation membrane designed by adopting a structure-function integrated scheme, the seesaw effect between high selectivity and high permeability is broken through, the flux bottleneck of a nano ceramic / micron metal porous separation membrane is broken through, and the actual wetting state is continuously and quantitatively described by a proposed aesthetic formula; the microporous membrane is high in strength, good in mechanical durability and free of coating stripping risk, upgrading and optimization of the metal oil-water separation membrane are accelerated, and technical support is provided for cost reduction and efficiency improvement of industrial mixed fluid filtration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous metal materials, and in particular relates to a control method for a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity. Background Art

[0002] With the rapid development of industrialization, crude oil and industrial oily wastewater leakage accidents occur frequently. The fields of petrochemical, daily chemical, biopharmaceutical, textile, leather, metal processing, etc. are in urgent need of efficient and environmentally friendly oil-water separation membranes. The new membrane material should have a high permeation flux for oil-water mixed fluids, that is, high "permeability"; at the same time, it should have a high oil-water separation efficiency, that is, selectivity.

[0003] On the one hand, according to Darcy's formula and its extended formula, the flux of liquid penetrating a porous body is related to the pore structure. The larger the pore size and the higher the porosity, the better the "permeability", that is, the more pores per unit area of ​​the porous body, the larger the pore size, and the thinner the pore wall, the greater the fluid flux. But on the other hand, a large number of surface wettability studies have qualitatively believed that the smaller the pore size, the higher the separation efficiency. Therefore, various separation membranes with nanometer-scale pore sizes are prepared to obtain high selectivity. Therefore, a seesaw effect (Trade-off effect) is formed, which is difficult to balance between permeation flux and separation accuracy, limiting the application of porous metal separation membranes.

[0004] Since the permeation flux of nanoporous metal separation membranes is very low, a large number of studies have adopted the idea of ​​"layering", where only a very thin layer of nanoporous structure on the surface of the substrate is used to achieve high selectivity, and the substrate layer uses a microporous structure with large pore size and high porosity to achieve high "permeability". Compared with the single-layer separation membrane at the nanoscale, the asymmetric structure of the surface nanoporous layer and the substrate microporous layer of the "layered" structure can reduce the transmembrane pressure, avoid deep pore blockage, and have a higher permeation flux. Therefore, a large number of studies have attempted to construct nanopores of various compositions, shapes, and sizes on metal porous substrates, such as patents with application numbers 202410525481.1, 202311152871.0, 202211183474.5, 202411041646.4, 202310757330.4, 201910439253.1, 201910737112.8, 202211589203.X, 202410862716.6, 202410985888.2, 202410735045.7, and 202410701476.1. However, the pore size of the nanoporous layer on the "layered" structure is very small. The pore size of the current commercial nano-ceramic / micron metal porous separation membrane can reach as low as 50nm, resulting in a maximum permeation flux of only 70% of the theoretical flux upper limit, which limits the further improvement of the permeation flux of the porous metal separation membrane. If the substrate microporous layer is given high selectivity, the flux bottleneck of the nano-ceramic / micron metal porous separation membrane will be broken. For example, patents with application numbers 202410701476.1, 202311025206.5, 202110922302.4, 202110178120.0, 202310727314.0, 202210990549.4, and 202410685233.3 prepare highly selective polymer coatings on the surface of the substrate microporous layer, so that the single-layer microporous membrane has both high selectivity and high "permeability". However, the polymer coating will inevitably swell and deform, oxidatively degrade, corrode or peel off during use, causing the selectivity of the membrane material to rapidly decay over time. In some working conditions, the separation membrane even needs to be replaced every day. The potential threat of some fluorine-containing coatings to water bodies also limits the application of this type of separation membrane.

[0005] Therefore, it is necessary to adopt a structural-functional integrated design solution to break the existing layered approach of relying on the nanoporous layer to achieve selectivity and the substrate microporous layer to achieve high "permeability". By optimizing the pore structure, the microporous substrate that originally only bears "permeability" is given high selectivity, breaking through the seesaw effect between high selectivity and high "permeability", and achieving a leap-forward improvement in the performance of metal oil-water separation membranes. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a control method for a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity in view of the deficiencies of the above-mentioned prior art. The method proposes a unique structure-function integrated microporous membrane. First, the phenomenological formula of the single-stage microporous structure for oil droplet selectivity in the target working condition is derived based on the gradient experimental results. Secondly, the optimal single-stage microporous structure with high selectivity is derived based on the formula. Finally, the same preparation technology and raw materials are used to achieve an optimized microscopic morphology, thereby obtaining a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for regulating a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity, characterized in that the method comprises the following steps:

[0008] Step 1: Perform a gradient experiment on the raw material using a pore-forming agent-assisted powder rolling technology to obtain multiple microporous membranes with different R / D values, where R and D are the pore wall thickness and pore size of the microporous membrane, respectively. Then, perform wetting state detection on multiple microporous membranes, and then substitute the detection results into the phenomenological formula: Calculations were performed, where f describes the thermodynamic stability of the intermediate wetting state in the fixed system, i.e., the selectivity of the microporous membrane to not permeate the oil droplets, and the values ​​of the empirical parameters a, b, and c were obtained;

[0009] Step 2: Substitute the values ​​of the empirical parameters a, b and c obtained in step 1 into the phenomenological formula for calculation to obtain the R / D value corresponding to the minimum f value under the target working condition;

[0010] Step 3: Use the same raw materials as in step 1 to prepare the materials according to the R / D value obtained in step 2, and then use the pore-forming agent-assisted powder rolling technology described in step 1 to prepare a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity.

[0011] The present invention discovers the influence of microporous structure on surface wettability in a series of intermediate wetting states based on the classical model of surface wettability, and proposes a theoretical model. In the classical wettability theory, the Cassie model describes the state of complete non-wetting on a rough surface, and the Wenzel model describes the state of complete wetting. The wetting state on the actual surface is usually between the above two extreme states. These intermediate wetting states are metastable states. There is no suitable theoretical formula to describe these actual intermediate wetting states, and their main parameters are difficult to measure experimentally, resulting in a large deviation between the existing theoretical and actual wetting states, which makes it difficult to guide the optimal design of the oil-water separation membrane and the active control of its performance.

[0012] The present invention adopts the morphological parameter R / D and determines the relevant parameters through experiments to establish the phenomenological relationship between the single-stage microporous structure and the selectivity for oil droplets, thereby realizing the continuous description of the intermediate wetting state under specific working conditions, and providing a simple and easy control method and theoretical basis for the design of single-stage microporous metal oil-water separation membrane.

[0013] In addition, the present invention also clarifies the existence of the optimal single-stage micropore structure. According to the second law of thermodynamics, in the system formed by oil droplets, microporous membranes and surrounding fluids, when the system is fixed, that is, the liquid composition, viscosity, flow rate, pressure on the membrane surface, membrane material composition, oil droplet type and size, external temperature and pressure, shape of pores on the microporous membrane surface, thickness of the microporous membrane, pore depth, ratio of connected pores to closed pores and other secondary variables are basically unchanged, the system free energy has a minimum value, and the intermediate wetting state corresponding to the minimum value is the most stable. At this time, the oil droplets are least likely to penetrate the microporous membrane, and the microporous membrane is most selective for oil droplets. From another perspective, the larger the R / D, the more stable the Cassie-Baxter state. However, due to the large proportion of solids on the mixed interface contacted by the oil droplets in the system, the underwater static oil contact angle (USCA) decreases, and the selectivity for the oil droplets decreases. On the contrary, when R / D increases, the USCA increases, but the fluid pressure that the microporous membrane can withstand decreases. If the fluid pressure is slightly disturbed, the oil droplets will penetrate the microporous membrane, causing the microporous membrane to be locally contaminated, thereby affecting the separation efficiency. Based on the above principle analysis, the present invention believes that for a fixed system under specific working conditions, there should be an optimal structure for the single-stage micropore structure.

[0014] From the perspective of improving the permeability of membrane materials, according to Darcy's formula and its extended formula, the flux of liquid penetrating porous bodies is related to the pore structure. The larger the pore size and the higher the porosity, the greater the flux. From the actual process of fluid penetrating membrane materials, the pore size and porosity represent the percentage of the membrane surface area occupied by the channels that the fluid can enter when the fluid contacts the surface of the membrane material, that is, the more pores per unit area of ​​the membrane material, the larger the pore size, and the thinner the pore wall, the greater the fluid flux; Darcy's formula uses the permeability coefficient B to characterize the pore structure of the membrane material. The factors affecting B are relatively complex and difficult to calculate theoretically, such as the pore size of the membrane material surface, the pore wall thickness, the number of pores per unit area, the composition, the membrane thickness, the pore curvature coefficient, the pore wall roughness, etc., so its specific value is usually determined by experiment. Since the B value is a passively measured parameter, it is not easy to achieve active control of the flux and the optimal design of the microscopic morphology of the membrane material.

[0015] The morphological parameter R / D proposed in the present invention can characterize both the permeability and selectivity of the microporous membrane surface. As mentioned above, R / D is used as the main variable in specific working conditions to quantitatively and actively regulate the wettability of the microporous membrane surface. At the same time, from the perspective of filtration flux, the parameters describing the micromorphology of membrane materials in Darcy's formula and its extended formula are all empirical constants, which require experimental determination and are difficult to achieve active control of flux. As mentioned above, R / D is used as the main variable in specific working conditions to quantitatively and actively regulate the flux of the microporous membrane. The smaller the R / D, the greater the permeation flux; the larger the R / D, the smaller the flux and the worse the permeability. Therefore, R / D becomes a bridge connecting the two theories of fluid movement and surface wettability, and provides a simple and easy control method and a quantitative theoretical basis for breaking through the seesaw effect between high selectivity and high permeability and preparing a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity.

[0016] In order to simplify the model and facilitate active control of the morphology, the R / D parameter ignores the influence of the internal pore curvature coefficient of the membrane material on the flux; because for a specific working condition, when the raw material powder, preparation technology and membrane material thickness of the microporous membrane are unchanged, the internal pore curvature coefficient is calculated according to the curvature coefficient (pressure loss coefficient) in the extension formula of the Darcy formula, and the influence of the internal pore curvature coefficient on the flux is not significant. That is, under the same working conditions, the material composition, membrane thickness and pore curvature coefficient of the gradient experiment and the optimal single-stage microporous structure in the present invention do not change significantly. At this time, the morphological parameter R / D becomes the main factor affecting the flux of the microporous membrane. However, in order to improve the flux, it is not feasible to increase R / D infinitely, because too high R / D will lead to low mechanical properties of the microporous membrane, microcracks may be generated under long-term water flow impact, and even in the preparation process, the porous skeleton collapses and cannot be sintered. Therefore, the selection of R / D should comprehensively consider the permeability, selectivity and mechanical strength of the membrane material.

[0017] Taking the above factors into consideration, the present invention uses a pore-forming agent-assisted powder rolling technology to conduct a gradient experiment on the raw material, substitutes the experimental results into the phenomenological formula, determines the values ​​of the empirical parameters a, b, and c, and obtains the phenomenological formula for the selectivity of the single-stage microporous structure to the oil droplet: The microporous structure is the value of R / D on the surface of the microporous membrane, where R and D are the pore wall thickness and pore size of the porous titanium separation membrane, respectively. It can characterize both the permeability and selectivity of the microporous membrane surface. The empirical parameters a, b, and c in the phenomenological formula depend on the thickness of the microporous membrane in the target working condition, the pore depth, the ratio of connected pores to closed pores, the shape of the pores on the surface of the microporous membrane, the surface tension between the microporous membrane, the oil droplets and the ambient fluid, the size of the oil droplets, the viscosity of the ambient fluid and other factors. For specific working conditions, and when the raw material powder, preparation technology and thickness of the microporous membrane remain unchanged, the above-mentioned secondary variables are usually fixed or change very little. Therefore, the empirical parameters a, b, and c can be simplified to the corresponding constants. Specifically, according to the second law of thermodynamics, oil The droplets, membrane materials and the surrounding fluid environment can be regarded as an energy system as a whole. For specific working conditions, the type and size of the oil droplets in the system, the composition of the membrane material, and the composition, viscosity, temperature and pressure on the membrane surface of the surrounding fluid basically do not change, and can be regarded as constants and concentrated on the empirical parameters a, b, and c. Secondly, for the morphological characteristics of the microporous membrane, when the raw material powder, preparation technology and thickness of the microporous membrane remain unchanged, the shape of the pores on the surface of the microporous membrane will not change significantly, and the depth of the pores inside the microporous membrane and the ratio of connected pores and closed pores will only fluctuate within a certain range, and will not significantly affect the wetting state of the microporous membrane. Therefore, for specific working conditions, the above two types of factors can be regarded as constants and concentrated on the empirical parameters a, b, and c. At this time, the intermediate wetting state of the system is mainly controlled by the morphological parameters R / D of the microporous membrane surface. When the working conditions change, the type and size of the oil droplets, the composition of the membrane material, and the composition, viscosity, temperature and pressure of the surrounding fluid on the membrane surface are different; or the raw material powder, preparation technology and thickness of the microporous membrane change, resulting in changes in the pore structure characteristics on the surface and inside of the microporous membrane, the empirical parameters a, b, c also change accordingly. The theoretical relationship between the empirical parameters a, b, c and the above-mentioned influencing factors is very complicated and has not yet been revealed. The method of determining the empirical parameters through gradient experiments in the present invention is relatively convenient and accurate, and can be extended to different working conditions and application fields to obtain the corresponding empirical parameters a, b, c.

[0018] For the intermediate wetting state that is difficult to describe theoretically, the phenomenological formula concentrates various minor variables that do not change significantly in specific working conditions and is represented by empirical parameters a, b, and c, highlighting the main influencing parameter R / D, and realizing the continuous quantitative description of the intermediate wetting state for the first time. The phenomenological formula skips the complex principles and formula derivations of various minor variables affecting the wetting state, and realizes the practical quantitative description of the intermediate wetting state, breaking the qualitative cognition that the smaller the pore size, the higher the separation efficiency, and becoming the theoretical support for giving single-stage microporous membranes high selectivity for oil droplets.

[0019] f describes the thermodynamic stability of the intermediate wetting state in the fixed system, that is, the selectivity of the microporous membrane to not penetrate the oil droplets. The smaller the f value, the higher the selectivity of the microporous membrane to the oil droplets, and the larger the f value, the lower the selectivity. The phenomenological formula proposed in the present invention describes the wetting state of the oil-water-solid three-phase system, and quantifies the selectivity of the microporous membrane to the oil droplets with the f value. The minimum value of f within the applicable range of the formula corresponds to the morphological parameter R / D, which describes the optimal selectivity that can be obtained by the single-stage microporous membrane when the oil-water mixed fluid composition, oil droplet size, flow rate, and temperature in the target working condition remain unchanged, and the material, thickness, and preparation technology of the microporous membrane remain unchanged, and the optimal single-stage micropore structure corresponding to it;

[0020] According to the phenomenological formula obtained in step one, the present invention derives the R / D corresponding to the minimum f value. The optimal single-stage micropore structure should satisfy the calculated R / D value. In the phenomenological formula of the single-stage micropore structure and the selectivity to oil droplets, the smaller the f value, the higher the selectivity of the microporous membrane. When the composition of the oil-water mixed fluid, the oil droplet size, the flow rate, and the temperature remain unchanged in the target working condition, the material, thickness, and preparation technology of the microporous membrane are not changed. The R / D corresponding to the minimum f value represents the optimal single-stage micropore structure under the target working condition, corresponding to the optimal selectivity that can be achieved by such a microporous membrane.

[0021] Finally, the present invention uses the same raw materials as in step one to prepare the materials according to the R / D value obtained in step two, and then adopts the powder rolling technology assisted by the pore-forming agent described in step one to achieve the optimal single-stage micron pore structure obtained in step two, thereby obtaining a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity.

[0022] Based on the classical model of surface wettability, the present invention has found that in a series of intermediate wetting states of a specific oil-water-solid three-phase system, there is an optimal wetting state for the selectivity of the microporous membrane to oil droplets. In the phenomenological formula proposed by the present invention, the minimum value of f describes this optimal state. Moreover, when the changes in each secondary variable are not significant and can be regarded as a constant, the influence of the morphological parameter R / D on the selectivity of the microporous membrane is very significant, and the fine-tuning of the morphological structure can significantly improve the selectivity of the microporous membrane. Therefore, it is difficult to obtain the optimal single-stage micropore structure through traditional trial and error iteration. The present invention directly obtains the optimal structure through calculation, which greatly accelerates the upgrade and optimization of metal oil-water separation membranes and provides simple and convenient technical support for industrial mixed fluid filtration to reduce costs and increase efficiency.

[0023] The above-mentioned method for regulating a single-stage microporous metal oil-water separation membrane with high permeability and high selectivity is characterized in that the value range of R / D in the gradient experiment described in step 1 is 0.59<R / D<1.36. In order to skip the theoretical derivation of the wetting state by various complex secondary variables and realize the practical description of specific working conditions, the phenomenological formula proposed in the present invention has a limited scope of application. When the limited range is exceeded, the wetting state of the system formed by the oil droplet, the microporous membrane and the surrounding fluid changes significantly when it crosses the critical value, and the phenomenological formula derived by the present invention can no longer describe its wetting state. Therefore, in the determination process of the empirical parameters a, b, and c, the morphological parameter R / D value of the gradient experiment should conform to the applicable range of the phenomenological formula, so that the measured empirical parameters can accurately and continuously describe each intermediate wetting state within the scope of use of the formula.

[0024] The above-mentioned method for regulating a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity is characterized in that at least three microporous membranes with different R / D values ​​are prepared in the gradient experiment in step 1. The present invention ensures that the values ​​of the empirical parameters a, b and c can be obtained by subsequent calculation by controlling the number of microporous membranes with different R / D values ​​in the gradient experiment.

[0025] The above-mentioned method for regulating a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity is characterized in that the method for detecting the wetting state in step 1 is: randomly selecting 40 points on the surface of the microporous membrane, measuring the diameter of the inscribed circle of the pore diameter and the minimum inscribed circle diameter of the surrounding pore wall, and taking the statistical average of the above 40 measured values ​​as the morphological parameter of the microporous membrane. The present invention ensures the accuracy of the data by controlling the detection method, and ensures that the single-stage microporous metal oil-water separation membrane finally prepared has both high permeability and high selectivity.

[0026] The above-mentioned method for regulating a single-stage microporous metal oil-water separation membrane with high permeability and high selectivity is characterized in that during the sintering process of the pore-forming agent-assisted powder rolling technology in step 1 and step 3, the upper and lower surfaces of the green sheet are fixed with smooth and flat ceramic sheets under pressure, and the pressure is 0.2MPa. The present invention controls the fixing method during the sintering process to limit the axial shrinkage deformation of the green sheet and reduce the pore structure deformation caused by the shrinkage deformation of the surface of the single-stage microporous metal oil-water separation membrane.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] 1. The present invention adopts a structural-functional integrated design scheme, simplifies various minor variables, clarifies the significant influence of the morphology parameter R / D on the selectivity of the microporous membrane, obtains the optimal single-stage micropore structure by calculation, gives the substrate micropore layer high selectivity, breaks the seesaw effect between high selectivity and high permeability, breaks through the flux bottleneck of nano-ceramic / micro-metal porous separation membranes, accelerates the upgrading and optimization of metal oil-water separation membranes, and provides simple and convenient technical support for industrial mixed fluid filtration to reduce costs and increase efficiency.

[0029] 2. The phenomenological formula proposed in the present invention realizes the continuous quantitative description of the intermediate wetting state for the first time. Since the actual wetting state is affected by various secondary variables, it is very complicated and difficult to describe theoretically, such as the thickness of the microporous membrane, the depth of the pore diameter, the ratio of connected pores to closed pores, the shape of the pores on the surface of the microporous membrane, the surface tension among the microporous membrane, the oil droplets and the environmental fluid, the size of the oil droplets, the viscosity and temperature of the environmental fluid, etc. The present invention proposes that for specific working conditions, and when the raw material powder, preparation technology and thickness of the microporous membrane remain unchanged, the complex influence principles and formulas of the secondary variables can be skipped, and the focus can be placed on the phenomenological parameters a, b and c. The phenomenological formula proposed in the present invention quantifies the actual wetting state in a simple and practical manner within the applicable scope, breaking the qualitative cognition that the smaller the pore diameter, the higher the separation efficiency, and becoming a theoretical support for giving single-stage microporous membranes high selectivity for oil droplets.

[0030] 3. Compared with the layered multi-stage metal oil-water separation membrane, the single-stage microporous metal oil-water separation membrane of the present invention has a simpler preparation process and is expected to be applied in large-scale industrial applications. However, the preparation process of the layered structure is complicated and the technical cost is high, making it difficult to obtain a large-area, continuous and defect-free layered multi-stage metal oil-water separation membrane.

[0031] 4. Compared with the fragile layered structure on the surface of the multi-stage metal oil-water separation membrane, the single-stage microporous metal oil-water separation membrane of the present invention has higher strength and better mechanical durability. The multi-stage metal oil-water separation membrane is prone to cracks or layered structure shedding when facing the impact of small solid particles in the mixed fluid, and the oil-water separation efficiency is therefore rapidly attenuated.

[0032] 5. Various polymer coating separation membranes in the present invention are prone to swelling and deformation, oxidation degradation, coating corrosion or peeling during use. Single-stage microporous metal oil-water separation membranes have higher strength and better mechanical durability. Facing the impact of small solid particles in the mixed fluid, it is not easy to produce cracks or porous structure shedding, and there is no risk of swelling and deformation, oxidation degradation, coating corrosion or peeling. It is widely used in high-temperature, high-salt, strong acid and alkali, and industrial oil-containing wastewater with complex components. In addition, single-stage microporous metal oil-water separation membranes have obvious advantages in the fields of biopharmaceuticals, daily chemical industry, etc., while the potential threat of existing fluorine-containing coatings to water bodies limits the application of polymer coating separation membranes.

[0033] 6. The present invention directly obtains the optimal structure through calculation, which greatly accelerates the upgrade and optimization of the metal oil-water separation membrane, provides a simple and convenient technical support for reducing costs and increasing efficiency in industrial mixed fluid filtration, and solves the problem that it is difficult to obtain the optimal single-stage micron pore structure through traditional trial and error iteration.

[0034] 7. The method of determining empirical parameters by gradient experiment in the present invention is relatively convenient and accurate, and can be extended to different working conditions and application fields.

[0035] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the design idea for the single-stage microporous metal oil-water separation membrane in the present invention and the prior art.

[0037] Figure 2 This is the SEM image of sample 1 obtained in Example 1 of the present invention.

[0038] Figure 3 This is the SEM image of sample 2 obtained in Example 1 of the present invention.

[0039] Figure 4 This is the SEM image of sample 3 obtained in Example 1 of the present invention.

[0040] Figure 5 This is the SEM image of sample 4 obtained in Example 1 of the present invention.

[0041] Figure 6 This is a tensile performance diagram of sample 4 obtained in Example 1 of the present invention.

[0042] Figure 7 This is a diagram of the bending resistance of sample 4 obtained in Example 1 of the present invention.

[0043] Figure 8 The actual pictures are of Sample 4 obtained in Example 1 of the present invention before and after the bending resistance test. DETAILED DESCRIPTION

[0044] Figure 1 The present invention and the prior art design ideas for single-stage microporous metal oil-water separation membranes. Figure 1 Figure a on the left shows that in the prior art, it is believed that the smaller the pore size, the higher the separation efficiency. Therefore, various separation membranes with nanometer-scale pore sizes are prepared to obtain high selectivity. However, this forms a seesaw effect that makes it difficult to balance the permeation flux and separation accuracy, limiting the application of porous metal separation membranes. Figure 1The middle figure b shows that the prior art believes that a layered approach is adopted, where only a very thin layer of nanoporous structure on the substrate surface is used to achieve high selectivity. The substrate layer uses a micron pore structure with a large pore size and high porosity to achieve high permeability. The very thin layer of nanoporous structure is usually achieved through a polymer coating, but the polymer coating will inevitably swell and deform, oxidatively degrade, and the coating will corrode or peel off during use, causing the selectivity of the membrane material to decay rapidly over time. In some working conditions, the separation membrane even needs to be replaced every day. Figure 1 Figure c on the right shows that the present invention breaks the existing layered approach of relying on a nanoporous layer to achieve selectivity and a substrate microporous layer to achieve high permeability. By optimizing the pore structure, the microporous substrate that originally only had permeability is endowed with high selectivity, thereby breaking through the seesaw effect between high selectivity and high permeability and achieving a leap in the performance of metal oil-water separation membranes.

[0045] Example 1

[0046] In this embodiment, for the target working conditions, a high temperature resistant and corrosion resistant porous titanium metal oil-water separation membrane is specifically required. The existing preparation process is a powder rolling technology assisted by a pore-forming agent, and the raw materials are titanium powder with a particle size of 40μm to 45μm and an NH3HCO3 pore-forming agent with a particle size of 45μm to 58μm.

[0047] This embodiment includes the following steps:

[0048] Step 1: A gradient experiment is conducted using a pore-forming agent-assisted powder rolling technique with titanium powder having a particle size of 40 μm to 45 μm and a NH3HCO3 pore-forming agent having a particle size of 45 μm to 58 μm, as follows:

[0049] (1) Gradient experiment 1:

[0050] The R / D of gradient experiment 1 was designed to be 0.8. Therefore, according to previous experience, 55% of titanium powder and 45% of pore-forming agent were uniformly mixed, and the green sheet with a thickness of 0.8 mm was obtained by powder rolling. Then, the upper and lower surfaces of the green sheet were fixed with smooth ceramic sheets at a pressure of 0.2 MPa and then vacuum sintered at 850 °C for 2 h. The vacuum degree was not greater than 9.0×10 -2 Pa, and obtain microporous membrane sample 1;

[0051] 40 points were randomly selected on the surface of sample 1 to measure the diameter of the inscribed circle of the pore and the minimum inscribed circle diameter of the surrounding pore wall. The statistical average of the above 40 measured values ​​was obtained. 49.9μm, The R / D coefficient of sample 1 is 0.81. Figure 2As shown, the morphology coefficient of gradient experiment 1 meets the applicable range of the phenomenological formula, and the empirical parameters a, b, and c determined based on this can accurately and continuously describe each intermediate wetting state;

[0052] The sample 1 was ultrasonically cleaned in acetone, ethanol, methanol and deionized water for 5 min to 10 min respectively, and the sample 1 was always placed in static deionized water after cleaning to eliminate the influence of air impurity adsorption. After testing, the wetting state of the separation membrane met the application range of the phenomenological formula and was superhydrophilic / underwater superoleophobic. Its underwater oil contact angle (oil phase is dichloromethane) was 143°±0.25°, f was 0.30, and the porosity was 54.9%;

[0053] (2) Gradient experiment 2:

[0054] The R / D of gradient experiment 2 was designed to be 1.0. Therefore, according to previous experience, 70% of titanium powder and 30% of pore-forming agent were uniformly mixed, and the green sheet with a thickness of 0.8 mm was obtained by powder rolling. Then, the upper and lower surfaces of the green sheet were fixed with smooth ceramic sheets at a pressure of 0.2 MPa and then vacuum sintered at 850 °C for 2 h. The vacuum degree was not greater than 9.0×10 -2 Pa, and obtain microporous membrane sample 2;

[0055] 40 points were randomly selected on the surface of sample 2 to measure the diameter of the inscribed circle of the pore and the minimum inscribed circle diameter of the surrounding pore wall. The statistical average of the above 40 measured values ​​was obtained. 49.9μm, The R / D coefficient of sample 2 is 1.02. Figure 3 As shown, the morphology coefficient of gradient experiment 2 meets the applicable range of the phenomenological formula, and the empirical parameters a, b, and c determined based on this can accurately and continuously describe each intermediate wetting state;

[0056] Sample 2 was ultrasonically cleaned in acetone, ethanol, methanol and deionized water for 5 min to 10 min respectively, and sample 2 was always placed in static deionized water after cleaning to eliminate the influence of air impurity adsorption. After testing, the wetting state of the separation membrane met the application range of the phenomenological formula and was superhydrophilic / underwater superoleophobic. Its underwater oil contact angle (oil phase was dichloromethane) was 150°±0.25°, f was 0.21, and the porosity was 45%;

[0057] (3) Gradient experiment 3

[0058] The R / D of gradient experiment 3 was designed to be 1.2. Therefore, according to previous experience, 60% titanium powder and 40% pore-forming agent were added and mixed evenly. The green sheet with a thickness of 0.8 mm was obtained by powder rolling. Then, the upper and lower surfaces of the green sheet were fixed with smooth ceramic sheets at a pressure of 0.2 MPa and then vacuum sintered at 850 °C for 2 h. The vacuum degree was not greater than 9.0×10 -2 Pa, and obtain microporous membrane sample 3;

[0059] 40 points were randomly selected on the surface of sample 3 to measure the diameter of the inscribed circle of the pore and the minimum inscribed circle diameter of the surrounding pore wall. The statistical average of the above 40 measured values ​​was obtained. 57.7μm, The R / D coefficient of sample 3 is 1.285. Figure 4 As shown, the morphology coefficient of gradient experiment 3 meets the applicable range of the phenomenological formula, and the empirical parameters a, b, and c determined based on this can accurately and continuously describe each intermediate wetting state;

[0060] Sample 3 was ultrasonically cleaned in acetone, ethanol, methanol and deionized water for 5 min to 10 min respectively, and sample 3 was always placed in static deionized water after cleaning to eliminate the influence of air impurity adsorption. After testing, the wetting state of the separation membrane met the application range of the phenomenological formula and was superhydrophilic / underwater superoleophobic. Its underwater oil contact angle (oil phase was dichloromethane) was 123.5°±0.25°, f was 0.68, and the porosity was 42.8%;

[0061] In summary, the test results of each gradient experiment are shown in Table 1;

[0062] Table 1

[0063] R / D f Porosity / % Gradient experiment 1 0.81 0.30 54.9 Gradient Experiment 2 1.02 0.21 45.0 Gradient Experiment 3 1.285 0.68 42.8

[0064] From the perspective of permeability, the smaller the R / D, the larger the pore size on the membrane surface, the thinner the pore wall, and the more pores per unit area, the greater the membrane permeation flux, the higher the porosity, and the better the permeability;

[0065] From the perspective of selectivity, the above results show that the relationship between the morphology coefficient R / D and the parameter f describing the permeability of the separation membrane is not linear, but should satisfy the phenomenological formula proposed by the present invention, wherein the sample in gradient experiment 2 has the smallest f value, the largest underwater oil contact angle, and the best selectivity for not permeating oil droplets, and the sample in gradient experiment 3 has the largest f value, the smallest underwater oil contact angle, and the worst selectivity for not permeating oil droplets;

[0066] Substitute the test results of the above gradient experiment into the phenomenological formula: Calculations were performed to obtain a=4.7, b=-9.0, c=4.5;

[0067] Step 2: Substitute the values ​​of the empirical parameters a, b, and c obtained in step 1 into the phenomenological formula for calculation and obtain When the first-order derivative is equal to 0, the corresponding f=0.19 is the minimum value in the entire applicable range. The R / D=0.96 corresponding to the minimum f value under the target working condition is obtained. When R / D=0.96, f reaches the minimum value. The actual wetting state of the microporous membrane at this time has the best selectivity for oil droplets. R / D=0.96 represents the optimal single-stage micropore structure under the target working condition. The gradient experimental results show that when the changes of various minor variables are not significant and can be regarded as constants, the influence of the morphological parameter R / D on f is very significant. The selectivity of the microporous membrane can be significantly improved by fine-tuning R / D.

[0068] Step 3: The same raw materials as those in step 1 are used to prepare the R / D=0.96 obtained in step 2, and then the pore-forming agent-assisted powder rolling technology described in step 1 is used to prepare the green sheet with a thickness of 0.8 mm. The green sheet is then fixed with smooth and flat ceramic sheets on both sides at a pressure of 0.2 MPa and then vacuum sintered at 850°C for 2 h, with a vacuum degree of no more than 9.0×10 -2 Pa, and obtain microporous membrane sample 4.

[0069] 40 points were randomly selected on the surface of sample 4 to measure the diameter of the inscribed circle of the pore diameter and the minimum inscribed circle diameter of the surrounding pore wall. The statistical average of the above 40 measured values ​​was obtained. 58.6μm, The R / D coefficient of sample 4 is 0.97. Figure 5 As shown, the morphology coefficient meets the applicable range of the phenomenological formula, and the empirical parameters a, b, and c determined based on this can accurately and continuously describe each intermediate wetting state;

[0070] Sample 4 was ultrasonically cleaned in acetone, ethanol, methanol and deionized water for 5 minutes to 10 minutes respectively, and sample 4 was always placed in static deionized water after washing to eliminate the influence of air impurity adsorption. After testing, the wetting state of the separation membrane was in line with the application range of the phenomenological formula, showing superhydrophilicity / underwater superoleophobicity, and its underwater oil contact angle (oil phase is dichloromethane) was 151.5°±0.25°, f was 0.18, and the porosity was 52.1%.

[0071] Sample 4 was subjected to mechanical durability test. Figure 6 , Figure 7 and Figure 8 , Figure 6The figure in the upper left corner shows sample 4 undergoing a tensile performance test, and the figure below shows the shape of sample 4 undergoing a tensile performance test. Figure 7 The lower right picture shows sample 4 undergoing a bending performance test. Figure 8 The upper middle side shows sample 4 before the bending performance test, and the lower middle side shows sample 4 after the bending performance test. Figure 6 and Figure 7 It can be seen that the tensile strength and bending strength can reach up to 135.7MPa and 66.4MPa, and the corresponding strain is very small. The results are shown in Table 2. The single-stage microporous metal oil-water separation membrane of sample 4 has higher strength, better mechanical durability and is not easy to deform. In the prior art, the fragile layered structure on the surface of the multi-stage metal oil-water separation membrane is prone to cracks or layered structure shedding when facing the impact of small solid particles in the mixed fluid, so the oil-water separation efficiency decays rapidly. In addition, various polymer coating separation membranes are prone to swelling and deformation during use, resulting in changes in surface morphology, affecting wettability and separation efficiency. It is reported that the deformation of the superhydrophilic polymer sponge has reached 55% at 0.2Mpa.

[0072] Table 2

[0073] Strength / MPa strain / % Tensile test 135.7 1.8 Bending test 66.4 6.0

[0074] In order to ensure that the secondary variables (composition, thickness, pore depth, ratio of connected pores to closed pores of the microporous membrane, shape of pores on the surface of the microporous membrane, etc.) do not change significantly, the raw material powders used in the gradient experiments and verification experiments of this embodiment are the same powders from the same batch, the thickness of the microporous membrane is 0.8mm±0.02mm, the preparation processes such as rolling speed, roller spacing, hopper powder feeding, vacuum degree and sintering system are unchanged, and the tests are carried out in the same test environment and equipment. The test conditions such as oil droplet composition, oil droplet size, deionized water composition, liquid viscosity, fluid temperature and pressure are the same, and the samples are always placed in static deionized water after washing to eliminate the influence of air impurity adsorption.

[0075] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for regulating a single-stage microporous metal oil-water separation membrane having both high permeability and high selectivity, characterized in that: The method comprises the following steps: Step 1: Perform a gradient experiment on the raw material using a pore-forming agent-assisted powder rolling technology to obtain multiple microporous membranes with different R / D values, where R and D are the pore wall thickness and pore size of the microporous membrane, respectively. Then, perform wetting state detection on multiple microporous membranes, and then substitute the detection results into the phenomenological formula: Calculations were performed, where f describes the thermodynamic stability of the intermediate wetting state in the fixed system, i.e., the selectivity of the microporous membrane to not permeate the oil droplets, and the values ​​of the empirical parameters a, b, and c were obtained; Step 2: Substitute the values ​​of the empirical parameters a, b and c obtained in step 1 into the phenomenological formula for calculation to obtain the R / D value corresponding to the minimum f value under the target working condition; Step 3: Use the same raw materials as in step 1 to prepare the materials according to the R / D value obtained in step 2, and then use the pore-forming agent-assisted powder rolling technology described in step 1 to prepare a single-stage microporous metal oil-water separation membrane with both high permeability and high selectivity.

2. The method for controlling a single-stage microporous metal oil-water separation membrane having both high permeability and high selectivity according to claim 1, characterized in that: The value range of R / D in the gradient experiment described in step 1 is 0.59<R / D<1.

36.

3. The method for controlling a single-stage microporous metal oil-water separation membrane having both high permeability and high selectivity according to claim 1, characterized in that: In the gradient experiment described in step 1, at least 3 microporous membranes with different R / D values ​​are prepared.

4. The method for controlling a single-stage microporous metal oil-water separation membrane having both high permeability and high selectivity according to claim 1, characterized in that: The method for detecting the wetting state in step 1 is: randomly selecting 40 points on the surface of the microporous membrane, measuring the diameter of the inscribed circle of the pore size and the minimum inscribed circle diameter of the surrounding pore wall, and taking the statistical average of the above 40 measured values ​​as the morphological parameter of the microporous membrane.

5. The method for controlling a single-stage microporous metal oil-water separation membrane having both high permeability and high selectivity according to claim 1, characterized in that: During the sintering process of the pore-forming agent-assisted powder rolling technology described in step 1 and step 3, smooth and flat ceramic sheets are used on both the upper and lower surfaces of the green sheet to be fixed by pressure at a pressure of 0.2 MPa.

Citation Information

Patent Citations

  • Preparation method of high-throughput switch type oil-water separation membrane based on natural bionics

    CN110237568A

  • A method for preparing a high-flux flat-panel ceramic membrane

    CN110368818B

  • Oil-water separation membrane and application thereof in perishable garbage treatment

    CN112973465A

  • A method for preparing a fluorinated oil-water separation membrane with high resistance to oil contamination and stability.

    CN113663528B

  • Polyethyleneimine Co-CAT-1 / graphene oxide composite separation membrane as well as preparation method and application thereof

    CN115350600A